2009
DOI: 10.1016/j.trstmh.2009.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile of 516 children affected by HIV in a tertiary care centre in northern India: 14 years of experience

Abstract: Increasing numbers of children affected by HIV are being recognised in northern India. The present study aimed to evaluate the clinical profile of 516 children affected by HIV at the Pediatric Allergy and Immunology Unit, Advanced Pediatric Center, Postgraduate Institute of Medical Education and Research, Chandigarh, India, during the period January 1994 to May 2008. In total, 454 children (327 boys and 127 girls) infected by HIV were analysed. The median age at presentation was 54 months. Of these children, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
14
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 21 publications
5
14
1
Order By: Relevance
“…Blood transfusion and vertical transmission comprised of 2.3% each which was comparable to a perspective on the current status of HIV epidemic in India by Solomon et al [9] Sircar et al and Singh S et al reported 12.1% and 5.7% seropositivity through blood transfusion which is almost (4.04%) equal to our study. [14,15] In our place of study, blood transfusion is given by kith and kin of a patient and no professional donors are used because of the awareness of HIV/Aids among general population. Also HIV testing of blood and blood products is done stringently to prevent spread through infected blood.…”
Section: Discussionmentioning
confidence: 99%
“…Blood transfusion and vertical transmission comprised of 2.3% each which was comparable to a perspective on the current status of HIV epidemic in India by Solomon et al [9] Sircar et al and Singh S et al reported 12.1% and 5.7% seropositivity through blood transfusion which is almost (4.04%) equal to our study. [14,15] In our place of study, blood transfusion is given by kith and kin of a patient and no professional donors are used because of the awareness of HIV/Aids among general population. Also HIV testing of blood and blood products is done stringently to prevent spread through infected blood.…”
Section: Discussionmentioning
confidence: 99%
“…9 In studies from India done by Singh S et al the common clinical features were fever (36.6%), respiratory infections (31.7%), lymphadenopathy (30%), hepatosplenomegaly (21.8%) and diarrhea illness (18%). 10 The clinical features of admitted HIV infected patients from Pakistan done by Siddique MH et al at tertiary level teaching hospital showed that the three most common clinical features were weight loss (59.6%), fever (42.3%) and diarrhea (38.8%). 11 These clinical features/OIs were similar to the presentation of our patients suggesting a similar strain of virus circulating in the region.…”
Section: Discussionmentioning
confidence: 99%
“…4 There is a paucity of literature on musculoskeletal manifestations of HIV infection in children. Various reviews on the clinical profile of HIV infection in children have not reported arthritis in children living with HIV as a major clinical manifestation [8][9][10][11] and there have been very few reports of arthritis in children with HIV infection (Table 2). [12][13][14][15] This may be because of the fact that these manifestations are uncommon or missed.…”
Section: Discussionmentioning
confidence: 99%